The Relevance of Maslahah Theory In Islamic Law To The Concept of Sabbe Satta Bhavantu Sukhitatta: A Comparative Study of The Implementation of Religious Moderation At Budhasari Vihara, Tulungagung - Eko Siswanto (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Religious moderation is one of the important paradigms in maintaining harmony within Indonesia's multicultural society. From the perspective of Islamic Law, the theory of maslahah is oriented toward realizing benefit and preventing harm as the main objectives of sharia (maqāṣid al-syarī'ah). Meanwhile, Buddhist teachings recognize the concept of Sabbe Satta Bhavantu Sukhitatta, which carries a universal meaning in the form of a prayer and hope that all living beings attain happiness, peace, and freedom from suffering. This study aims to analyze the relevance of maslahah theory in Islamic Law to the concept of Sabbe Satta Bhavantu Sukhitatta and its implementation in the practice of religious moderation at Budhasari Vihara, Tulungagung. The study uses a qualitative approach with a field research design combined with a literature study. Data were obtained through observation, in-depth interviews with vihara administrators, religious figures, and the surrounding community, as well as documentation, and were then analyzed using descriptive-comparative analysis techniques with normative and sociological approaches. The results show that maslahah theory and the concept of Sabbe Satta Bhavantu Sukhitatta meet at points of universal human values, namely the protection of life, respect for human dignity, tolerance, compassion, and efforts to realize social peace. The implementation of both concepts is reflected in the practice of interfaith dialogue, openness to the community, social activities, and interfaith cooperation that take place at Budhasari Vihara, Tulungagung. This study concludes that maslahah theory in Islamic Law has substantive relevance to the concept of Sabbe Satta Bhavantu Sukhitatta as an ethical foundation for building religious moderation, so that both can become a shared paradigm in strengthening harmony, social integration, and a harmonious national life amid a plural society.